2021
DOI: 10.1007/s00787-020-01709-y
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion recognition impairment predicts social and emotional problems in children with (subthreshold) ADHD

Abstract: Children with attention-deficit/hyperactivity disorder (ADHD) symptoms often experience social and emotional problems. Impaired facial emotion recognition has been suggested as a possible underlying mechanism, although impairments may depend on the type and intensity of emotions. We investigated facial emotion recognition in children with (subthreshold) ADHD and controls using a novel task with children’s faces of emotional expressions varying in type and intensity. We further investigated associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…Children with ADHD showed impaired AE, compared to normal controls [ 17 , 18 , 19 ], either assessed as a trait using parent reports [ 20 ] or state assessed with affective responses to vignettes [ 17 ]. Furthermore, the difficulties in emotion recognition, involved in AE [ 16 ], have been reported in youths with ADHD [ 21 ]. Maoz et al (2019) [ 22 ] showed a global deficit in both the components of empathy in its self-report form.…”
Section: Introductionmentioning
confidence: 99%
“…Children with ADHD showed impaired AE, compared to normal controls [ 17 , 18 , 19 ], either assessed as a trait using parent reports [ 20 ] or state assessed with affective responses to vignettes [ 17 ]. Furthermore, the difficulties in emotion recognition, involved in AE [ 16 ], have been reported in youths with ADHD [ 21 ]. Maoz et al (2019) [ 22 ] showed a global deficit in both the components of empathy in its self-report form.…”
Section: Introductionmentioning
confidence: 99%
“…Children and adolescents with ADHD also exhibit an impaired emotion recognition ability and a nonverbal receptive language deficit [ 5 , 48 , 49 ], which denotes a difficulty in detecting and interpreting social clues and generates impaired social interactions and interpersonal problems. In particular, individuals with ADHD are significantly poorer in identifying emotional expressions, especially the negative effects of fear, anger and sadness, likely originating from a primary deficiency in encoding social cues and selectively inhibiting irrelevant information in ADHD [ 43 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several studies have found similar difficulties in children with ADHD (e.g. Chronaki et al, 2015;Jusyte et al, 2017;Sjöwall et al, 2013;Staff et al, 2022) and DLD (e.g. Griffiths, et al, 2020;Spackman et al, 2005).…”
Section: Discussionmentioning
confidence: 89%